Protective Immunity against SARS Subunit Vaccine Candidates Based on Spike Protein: Lessons for Coronavirus Vaccine Development - Khalaj-Hedayati, Atin (J Immunol Res, 2020)
The recent outbreak of the novel coronavirus disease, COVID-19, has highlighted the threat that highly pathogenic coronaviruses have on global health security and the imminent need to design an effective vaccine for prevention purposes. Although several attempts have been made to develop vaccines against human coronavirus infections since the emergence of Severe Acute Respiratory Syndrome coronavirus (SARS-CoV) in 2003, there is no available licensed vaccine yet. A better understanding of previous coronavirus vaccine studies may help to design a vaccine for the newly emerged virus, SARS-CoV-2, that may also cover other pathogenic coronaviruses as a potentially universal vaccine. In general, coronavirus spike protein is the major antigen for the vaccine design as it can induce neutralizing antibodies and protective immunity. By considering the high genetic similarity between SARS-CoV and SARS-CoV-2, here, protective immunity against SARS-CoV spike subunit vaccine candidates in animal models has been reviewed to gain advances that can facilitate coronavirus vaccine development in the near future.